Constru??o de pr?ticas pedag?gicas nos anos iniciais do ensino fundamental: possibilidades did?ticas em educa??o ambiental do campo para professores da Chapada Diamantina - Ribeiro, Cristina Alice Cunha (2024)
The work presented here is part of the area of Environmental Education, of the Professional Master's Program in the National Network for Teaching Environmental Sciences (PROFCIAMB/UEFS), and is linked to the Environment and Society research line. We analyzed the data referring to the school context with regard to the objective of developing a pedagogical proposal for teacher training for the initial years of Elementary School, in order to develop learning in dialogue with Environmental Education and its relations with local knowledge, having as its objective landscape elements of the Serra do Ara?jo Conservation Unit (UCSA). To achieve this end, we used case study as a methodology, with conversation circles, guided tours and pedagogical workshops being held with the purpose of analyzing how elements of the UCSA landscape can be used in the creation of didactic sequences by teachers, in order to expand explanations regarding the relationships between nature and society, taking into account landscape, environmental and cultural values. To this end, we also appropriate the literature that dialogues with our research topic, through the works of theorists such as Sacrist?n, Arroyo, Layrargues, Leff, Sauv?, Vygostsky, among others. This study hypothesized that the same landscape elements at UCSA can generate different didactic sequences, because each teacher has different life experiences and this certainly reflects on the way each one plans their pedagogical practice. In view of this, a study describing and analyzing the results found is presented, associated with proposals for studies on the subject, with the aim of building a pedagogical proposal for teachers in the initial years of Elementary School, with UCSA as a spatial focus, the in order to develop learning in dialogue with Environmental Education and its relationships with local knowledge. The research results direct us to discussions around the SDs constructed by teachers, as well as their statements about methodological stages and experiences during the research. We conclude that the entire research path, combined with pedagogical constructions ? systematized SDs ? translates into a set of practices that dialogue with Environmental Education, when linked and explored elements of local culture, reflected in the various forms of popular knowledge, in the knowledge of a scientific nature and dialogues with groups outside the school context, within a critical perspective of encouraging reflection around the diverse and complex relationships between man and nature.